Enhancing the Knowledge of Elderly Posyandu Cadres in Sukoharjo Village, Malang City Through Aromatherapy Telon Oil Making Training - Andika, Venny Kurnia; Sugiyanto, Sugiyanto; Agustina, Yolanda (Journal of Community Practice and Social Welfare, 2024)
Elderly individuals experience natural aging, which is associated with frailty syndrome. The prevalence of frailty syndrome ranges from 7% in those over 65 years old to 30% in those over 80 years old. Around 35% of the global elderly population and 50% of elderly individuals in Indonesia report sleep quality issues. One non-pharmacological therapy that can be applied to elderly individuals with sleep difficulties is aromatherapy using essential oils. The aim of this community service activity is to enhance the knowledge and skills of Posyandu cadres in Sukoharjo Village, Malang City, regarding the benefits of essential oils and the process of making aromatherapy telon oil. The method used in this activity includes providing information on essential oils and the process of creating aromatherapy telon oil, followed by a practical session on making lavender-based aromatherapy telon oil for Posyandu cadres. The community service activity is conducted in three stages: the first stage involves a presentation on the health benefits of essential oils, the second stage focuses on the process of making aromatherapy telon oil, and the third stage includes a hands-on practice session followed by an evaluation of the participants' knowledge. The evaluation results show a 64.65% increase in the participants’ knowledge, based on pretest and post-test scores. This improvement indicates that the information regarding the health benefits of essential oils and the method for making aromatherapy telon oil is well understood by the Posyandu cadres.